Angle-selective all-dielectric Huygens' metasurfaces. (28th September 2017) - Arslan, D; Chong, K E; Miroshnichenko, A E; Choi, D-Y; Neshev, D N; Pertsch, T; Kivshar, Y S; Staude, I
Abstract: We experimentally and numerically study the angularly resolved transmission properties of dielectric metasurfaces consisting of silicon nanodisks which support electric and magnetic dipolar Mie-type resonances in the near-infrared spectral range. First, we concentrate on Huygens' metasurfaces which are characterised by a spectral overlap of the fundamental electric and magnetic dipole resonances of the silicon nanodisks at normal incidence. Huygens' metasurfaces exhibit a high transmitted intensity over the spectral width of the resonances due to impedance matching, while the transmitted phase shows a variation of 2 π as the wavelength is swept across the width of the resonances. We observe that the transmittance of the Huygens' metasurfaces depends on the incidence angle and is sensitive to polarisation for non-normal incidence. As the incidence angle is increased starting from normal incidence, the two dipole resonances are shifted out of the spectral overlap and the resonant features appear as pronounced transmittance minima. Next, we consider a metasurface with an increased nanodisk radius as compared to the Huygens' metasurface, which supports spectrally separate electric and magnetic dipole resonances at normal incidence. We show that for TM polarisation, we can shift the resonances of this metasurface into spectral overlap and regain the high resonant transmittance characteristic of Huygens' metasurfaces at a particular incidence angle. Furthermore, both metasurfaces are demonstrated to reject all TM polarised light incident under angles other than the design overlap angle at their respective operation frequency. Our experimental observations are in good qualitative agreement with numerical calculations.